Kajian Efisiensi Pembangunan Waduk Kuwil Untuk Reduksi Banjir Di Manado Akibat Sungai Tondano - Pua, Michael; Sumarauw, Jeffry S. F.; Manoppo, Fabian J. (JURNAL ILMIAH MEDIA ENGINEERING, 2017)
In order to improve the protection of people from water damages disaster, the fulfillment of water sufficiency for most people and farming people, then one way to support the above is to create a multipurpose dam that is Kuwil dam, in addition useful for controlling the ultimate flood-witch This is often the case in Manado and its surroundings. Also, in order to control the flood of Manado City and its surroundings, serious and integrated handling is needed from various related parties. One of the main river that flows Manado City is Tondano river. To control flooding, other than through non-physical effort, physical effort from construction technology is required. The selection of flood control buildings must be carefully calculated, the advantages, disadvantages, benefits and controls. Dam is an irrigation infrastructure that has a very high risk if it fails. Therefore, prior to the construction of dam, there are 3 (three) certifications that must be owned by the prospective owner of the dam. The certification in question is design certification aimed at testing the feasibility of the design details submitted by the consultant team; filling certification that aims to test the physical worthiness of the dam; and operational certification that aims to check the physical viability of the dam over a period of time.Kuwil dam is located across the Tondano river precisely in Kuwil Village, Kalawat Subdistrict, North Minahasa Regency, North Sulawesi Province which is ± 20 km from Manado city, the capital of North Sulawesi Province.The aims of this research are:  To find out the effectiveness of Kuwil dam as a flood reducer in Manado and in order to know the stability of dam  for spillway building due to flood discharge.Method used in this research are data collection. The data is used as a basis for calculation of stability and technical planning. From the rainfall data obtained, hydrological analysis resulted in flood discharge plan, which then processed again to find the amount of flood routing which result is used to determine the elevation of crest spillway. Hydrological analysis for dam planning, covering four things, namely: The inflow that fills the dam, flood plans to determine the capacity and dimensions of spillway buildings,  dam count and  outflow to determine the retrieval building. The calculation of flood debit were proceed  using HEC-HMS Program software.Results revealed that Kuwil’s dam  gives a significant impact for Manado city and its surroundings because it can reduce flood. The efficiency of flood control in Manado and the surrounding could be done by setting the operation pattern of the reservoir. Keywords: water damage disaster, flood , dam, HEC-HMS program, efficiency of flood control